2021
DOI: 10.1016/j.celrep.2021.109376
|View full text |Cite
|
Sign up to set email alerts
|

Human oncoprotein 5MP suppresses general and repeat-associated non-AUG translation via eIF3 by a common mechanism

Abstract: Highlights d eIF5-mimic protein (5MP) binds eIF2 and eIF3 through a domain homologous to eIF5 d 5MP displaces eIF5 through eIF3c within the PIC to increase initiation accuracy d 5MP suppresses general and repeat-associated non-AUG translation d In a fly FXTAS disease model, 5MP represses neuronal toxicity and enhances lifespan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…Long repetitive sequences have been shown to stimulate translation initiation upstream; more details on the molecular processes and associated disease etiology can be found in several reviews dedicated to this topic [ 69 71 ]. However, it is important to note that during RAN translation, recognition of non-AUG codons seems to occur via the standard cap-dependent mechanism and involves canonical initiation factors and regulators [ 72 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long repetitive sequences have been shown to stimulate translation initiation upstream; more details on the molecular processes and associated disease etiology can be found in several reviews dedicated to this topic [ 69 71 ]. However, it is important to note that during RAN translation, recognition of non-AUG codons seems to occur via the standard cap-dependent mechanism and involves canonical initiation factors and regulators [ 72 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we showed that, except for AUG, Ψ in the second NUG codon base strongly enhances initiation through increased base pairing to the mismatched start codon, while 5mC in the first base of a CUG codon diminishes initiation in a context-dependent manner. While non-AUG translation is known to be regulated by trans-acting factors independently of the codon types ( 13 , 25 , 39 ), codon-specific regulation has not been reported. To our knowledge, this is the first report that shows that the chemical modification of near-cognate start codons can specifically alter initiation frequency and hence recode translation initiation.…”
Section: Discussionmentioning
confidence: 99%
“…(a-c) arrow with a dotted line, change in place and/or in time; solid lines show induction or inhibition of certain processes translation but its role in RAN translation regulation is yet to be defined (Cate, 2017;Hashem et al, 2013). Further studies demonstrating the role of eiF3 in both canonical and RAN translation initiation on CGG exp indicated that human oncoprotein eIF5-mimic (5MP) displaces eIF5 through eIF3c subunit within the PIC and thus affects both modes of translation via increasing the accuracy of translation initiation (Singh et al, 2021;Tang et al, 2017). In addition, it was shown that overexpression of Drosophila 5MP homolog in FXTAS flies reduced RAN peptides-mediated toxicity (Singh et al, 2021).…”
Section: Ran Translationmentioning
confidence: 99%
“…Further studies demonstrating the role of eiF3 in both canonical and RAN translation initiation on CGG exp indicated that human oncoprotein eIF5-mimic (5MP) displaces eIF5 through eIF3c subunit within the PIC and thus affects both modes of translation via increasing the accuracy of translation initiation (Singh et al, 2021;Tang et al, 2017). In addition, it was shown that overexpression of Drosophila 5MP homolog in FXTAS flies reduced RAN peptides-mediated toxicity (Singh et al, 2021). Recently, Sonobe et al (2021) developed a new C. elegans model of C9-ALS/FTD.…”
Section: Ran Translationmentioning
confidence: 99%